LEVEL OF PHYSICAL FITNESS OF VOLLEYBALL PRACTICAL ADOLESCENTS (Fiep Bulletin - online, 2019)
The objective of the study was to analyze the level of physical fitness related to performance in adolescents practicingvolleyball. This is a descriptive research of quantitative approach with a sample of 20 adolescents with ages between 11 and 17years, practicing volleyball in the city of Patos-PB. Six tests were used: agility, flexibility, upper and lower limb power, localizedmuscular endurance, velocity, and weight and height measurements, following the protocol of the Brazilian Sport Project Manual- PROESP-BR. It was observed that the evaluated ones have average age of 13,6 years, weight 57,0kg, height 1,60m. In theflexibility test, 35.0% are in the risk zone and 65.0% are in the healthy zone, in the abdominal resistance test, 20.0% are in the riskzone and 80.0% are in the healthy zone. In the speed test, 45.0% are above desirable and 55.0% are below desirable. In theagility test, 10.0% are above desirable and 90.0% are below desirable. In the explosive strength test of lower limbs, 80.0% areabove desirable and 20.0% are below desirable. In the explosive strength test of lower limbs, 60.0% are above desirable and40.0% are below desirable. We conclude that the results of this study presented in some tests the expected results and in others itneeds to have a greater incentive in the training of the abilities.